Cross-border cooperation: modeling of project decisions at reconstruction of municipal heating systems - Харитонов, Юрий Николаевич (Technology audit and production reserves, 2015)
The integration processes, associated with the desire of Ukraine to the European Union, require the reduction of technical and technological level of the different economic sectors in accordance with regulatory measures accepted in the Union. This problem is important for municipal heating systems. Among the most common problems related to the heating systems of municipalities of Ukraine, which is largely determined by the relevance of the formation and implementation of projects and programs of reconstruction, there are following: technical and technological, environmental and socio-economic. Reconstruction and modernization of municipal heating systems is based on models and mechanisms of the theory of project management. The models of the theory of project management related to projects of reconstruction of municipal power systems are considered. It is shown that in the framework of project management on the problems of reconstruction of municipal heating systems is not scientifically based and comprehensive solution. The model of management of reconstruction projects for municipal heating systems is developed on the basis of the use of established knowledge base and database serving as an artefactual design solutions obtained by each of the parties on their own cross-border cooperation.